Alcohol and other Drugs codependency: the mutual help as a vector of resilience in codependent families - Avila, Maria Roseli Rossi; Krüger, Rolf Roberto (Vox Scripturae - Revista Teológica Internacional, 2017)
This article discusses the process of producing and strengthening resilience in families who are codependent on alcohol and drugs and participate in mutual help groups. It argues that mutual help is a vector of strengthening resilience for these families and points to social relations and spirituality as important factors for such empowerment. The study is justified by its social and academic relevance, provides theoretical / practical interlocution and allows the construction of knowledge that has not yet been explored by previous studies in the area addressed. As an introduction, it presents patterns of consumption of alcohol and other drugs in the world and in Brazil. Then it discusses the profile of mutual help groups regarding inherent spirituality, specificities, and sociabilities; theories and concepts about chemical dependency, codependency and mutual help relations. Finally, it presents the results of a case study conducted between June and September 2015 with users and leaders of the mutual help groups of the Blue Cross in Brazil in Blumenau / SC, as well as comments from the authors on the subject. The results of this research can provide support for concrete actions in the area of chemical dependency, therapeutic community, mutual help groups and in the social service area of Theology.